2009
DOI: 10.1007/s00366-009-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of tensegrity structures using parametric analysis and stochastic search

Abstract: Tensegrity structures are lightweight structures composed of cables in tension and struts in compression. Since tensegrity systems exhibit geometrically nonlinear behavior, finding optimal structural designs is difficult. This paper focuses on the use of stochastic search for the design of tensegrity systems. A pedestrian bridge made of square hollow-rope tensegrity ring modules is studied. Two design methods are compared in this paper. Both methods aim to find the minimal cost solution. The first method appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The equilibrium between tension and compression forces is responsible for the structural stability and load bearing capacity of tensegrities. Previous studies have found that the self-stress level initially introduced in tensegrity members before applying loads have a direct impact on both the weight and the deflection of the tensegrity footbridge [26,27]. This suggests that initial self-stresses, together with the cross-sectional areas of tensioned and compressed members are the key design parameters that affect the structural performance and cost of a tensegrity structure.…”
Section: Design Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium between tension and compression forces is responsible for the structural stability and load bearing capacity of tensegrities. Previous studies have found that the self-stress level initially introduced in tensegrity members before applying loads have a direct impact on both the weight and the deflection of the tensegrity footbridge [26,27]. This suggests that initial self-stresses, together with the cross-sectional areas of tensioned and compressed members are the key design parameters that affect the structural performance and cost of a tensegrity structure.…”
Section: Design Variablesmentioning
confidence: 99%
“…Recently, Motro [25] proposed a new family of tensegrity modules called "tensegrity rings" that can be assembled in a "hollow rope". As shown in previous work [26,27], the concept of "hollow rope" shows promise for architecture and civil engineering applications such as footbridges. Few studies on design and optimization of tensegrity structures have been observed to be of practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, designing a tensegrity structure is a challenging task due to a complex coupled nonlinear behavior that is closely related to the topology explored. Furthermore, there are no generally accepted design guidelines for tensegrity structures except a few studies underlying critical parameters of their structural behavior such as self-stress and the strut-to-cable stiffness ratio [9,10]. Due to the complexity of the design task, the use of stochastic search methods or other optimization techniques has been explored [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are no generally accepted design guidelines for tensegrity structures except a few studies underlying critical parameters of their structural behavior such as self-stress and the strut-to-cable stiffness ratio [9,10]. Due to the complexity of the design task, the use of stochastic search methods or other optimization techniques has been explored [10,11]. However, no study takes into account shape changes such as deployment and actuation schemes for the design of the tensegrity structure.…”
Section: Introductionmentioning
confidence: 99%
“…Although tensegrity rings are composed of a single strut circuit, their deployment can be completed without strut collision. The "hollow rope" concept shows promise for architecture and civil engineering applications such as pedestrian bridges (Rhode-Barbarigos et al 2010b;Rhode-Barbarigos et al 2010a). However, its application for a deployable footbridge has not been explored.…”
Section: Introductionmentioning
confidence: 99%